Lamprey metamorphosis: Thyroid hormone signaling in a basal vertebrate. (25th December 2017) - Manzon, Richard G.; Manzon, Lori A.
Abstract: As one of the most basal living vertebrates, lampreys represent an excellent model system to study the evolution of thyroid hormone (TH) signaling. The lamprey hypothalamic-pituitary-thyroid and reproductive axes overlap functionally. Lampreys have 3 gonadotropin-releasing hormones and a single glycoprotein hormone from the hypothalamus and pituitary, respectively, that regulate both the reproductive and thyroid axes. TH synthesis in larval lampreys takes place in an endostyle that transforms into typical vertebrate thyroid tissue during metamorphosis; both the endostyle and follicular tissue have all the typical TH synthetic components found in other vertebrates. Furthermore, lampreys also have the vertebrate suite of peripheral regulators including TH distributor proteins (THDPs), deiodinases and TH receptors (TRs). Although at the molecular level the components of the lamprey thyroid system are ancestral to other vertebrates, their functions have been largely conserved. TH signaling as it relates to lamprey metamorphosis represents a particularly interesting phenomenon. Unlike other metamorphosing vertebrates, lamprey THs increase throughout the larval period, peak prior to metamorphosis and decline rapidly at the onset of metamorphosis; patterns of deiodinase activity are consistent with these increases and declines. Moreover, goitrogens (which suppress TH levels) initiate precocious metamorphosis, and exogenous TH treatment blocks goitrogen-induced metamorphosis and disrupts natural metamorphosis. Despite this clear physiological difference, TH action via TRs is consistent with higher vertebrates. Based on observations that TRs are upregulated in a tissue-specific fashion during morphogenesis and the finding that lamprey TRs upregulate genes via THs in a fashion similar to higher vertebrates, we propose the following hypothesis for further testing. THs have a dual role in lampreys where high TH levels promote larval feeding and growth and then at the onset of metamorphosis TH levels decrease rapidly; at this time the relatively low TH levels function via TRs in a fashion similar to that of other metamorphosing vertebrates. Graphical abstract: Highlights: Lamprey thyroid hormone signaling is ancestral, somewhat unique, but conserved. Lamprey metamorphosis coincides with a decline in serum thyroid hormone levels. Goitrogens initiate and exogenous thyroid hormones disrupt lamprey metamorphosis. High levels of thyroid hormones promote larval lamprey feeding and growth. Low thyroid hormone levels may regulate lamprey metamorphosis via nuclear receptors.